A bicarbonate-rich liquid condensed phase in non-saturated solutions in the absence of divalent cations - Bewernitz, Mark A.; Ginder-Vogel, Matthew; Wolf, Stephan E.; Seto, Jong; Constantz, Brent R. (Frontiers in Bioengineering and Biotechnology, 2024)
Bicarbonate (HCO3 -) and sodium (Na + )-containing solutions contain droplets of a separate, bicarbonate-rich liquid condensed phase (LCP) that have higher concentrations of HCO3 -relative to the bulk solution in which they reside. The existence and composition of the LCP droplets has been investigated by nanoparticle tracking analysis, nuclear magnetic resonance spectroscopy, refractive index measurements and X-ray pair distribution function analysis. The bicarbonate-rich LCP species is a previously unaccounted-for, ionic phenomenon which occurs even in solutions with solely monovalent cations. Its existence requires re-evaluation of models used to describe and model aqueous solution physicochemistry, especially those used to describe and model carbonate mineral formation. Commented [MB2]: Revised text due to suggestion by R2. Commented [MB3]: Figure updated to reflect R1,R2 suggestions. The "part C" figure was labeled appropriately to indicate the the Refractive indices for LCP mid range and low range were esti-mated… not mathematically determined.